Activating and tuning basal planes of MoO2, MoS2, and MoSe2 for hydrogen evolution reaction. Issue 43 (15th October 2015) - Lin, Shi-Hsin; Kuo, Jer-Lai
Abstract : Inert basal planes of transition metal dichalcogenides can be activated by creating defects, resulting in better performance for hydrogen evolution reaction. Abstract : We investigated the defected two-dimensional materials MoX2 (X = O, S, Se) for hydrogen evolution reaction by first principles calculations. While the basal plane is inert for pristine MoX2, we found that the defected MoX2 can adsorb hydrogen atoms at defect sites, with appropriate adsorption energies for hydrogen evolution. By analyzing density of states and charge density, we showed that a dangling bond state slightly below the Fermi energy emerges when a defect is created. We proposed that this state is responsible for hybridizing with the hydrogen atom 1s state and hence the adsorption. Knowing the mechanism, we further considered tuning the reaction using adatoms (several first-row transition metals, B, C, N, O). We found that C and O adatoms can make defected MoX2 ideal for hydrogen evolution at higher defect levels (H coverage).